Gaya komunikasi kepemimpinan transformasional dalam masa perubahan organisasi: Sebuah tinjauan literatur - Pramana, Pinandito Dhirotsaha; Anwar, Aan Almaidah (Directorate General of Taxes, 2024)
The Directorate General of Taxes (DJP) is undertaking Tax Reform Volume III, which encompasses a focus on the reform of Human Resources (HR). The management of organizational change is inherently complex, and issues persist regarding the dynamics between superiors and subordinates at DJP. This study aims to furnish insights into change management from a communicative standpoint, specifically identifying the most suitable leadership communication styles to implement during the change process. The research employs a literature review methodology. Findings reveal that the transformational leadership communication style is the most effective for managing change. Communication styles that are devoid of emotional bias, empathetic, and allows for two-way communication are generally favored by subordinates. Training aimed at enhancing leadership communication competencies represents a feasible solution to equip individuals with the necessary skills to cultivate an optimal work environment